SOSIALISASI PEMANFAATAN AZOLLA MICROPHYLLA SEBAGAI PAKAN TERNAK PADA LAHAN SEMPIT - Sembiring, Meriksa; Risdawati Br Ginting (JURNAL PENGABDIAN MANDIRI, 2024)
Community outreach on the use of Azolla microphylla as animal feed on limited land in Sei Mencirim village, Sunggal district. Deli Serdang Regency, Sumatra province in January 2023. The aim of carrying out community service is to introduce the technique of developing Azolla microphyla using the organic hormone 'bean sprouts' to provide chicken farming to the community which is cheap, makes coercive feed efficient and is environmentally friendly. The specific target of this community service is the development of the Azolla microphylla plant as animal feed which can be substituted with commercial feed which at a fairly high price, can save feed costs. It is hoped that the implementation of this community service will ensure that the public will gain knowledge about the development of the Azolla microphylla plant using organic hormone media with the basic ingredients of "Bean Sprouts". So far, animal feed has been in the form of 100% commercial feed purchased from poutry shops, so this has become a problem for breeders. high price... Even though this plant is easy to grow even on limited land. The method used is implementing community service in the form of lectures and discussions, direct practice in planting Azolla microphylla and later practicing how to feed chickens.